Effect of community education in an integrate control for Triatoma dimidiata (Hemiptera: Reduviidae) - Soto LÃ³pez, Julio David; Monroy, MarÃa Carlota; Dorn, Patricia; Castellanos, Salvador; Lima, Raquel; Rodas, Antonieta (Revista Cubana de Medicina Tropical, 2020)
Introduction: The Mesoamerican endemic specie Triatoma dimidiata is the main vector of Chagas disease in Central America, after the elimination of an introduced vector Rhodnius prolixus. The traditional method of vector control using insecticides results in reinfestation. An integrated Ecohealth approach, including education, house improvements and domestic animal management was shown effective for long-term control of T. dimidiata, and it was applied in several villages in Guatemala. Objective: To evaluate the changes in community practices after an Ecohealth intervention in La Prensa, Olopa Chiquimula. Methods: Through three surveys, we measured risk factors associated withT. dimidiata infestation, the infestation index, blood sources of T. dimidiata, the presence of Trypanosoma cruzi were analyzed using PCR. Statistics analysis included Wilcoxon signed-rank tests, Mc-Nemar test, Chi-square test and Fisher exact test to compare the surveys. Results: Over the years, risk factors associated with the presence of T. dimidiata and population density of the vector were observed. We found a decrease in consumption of human blood and the parasite in the vector population. However, we found the consumption of bird blood meal increased. Conclusions: Our results provide evidence that an ecohealth approach for an endemic Chagas vector has impact on reducing vector-human contact, possibly by influencing people’s behavior. Increasing the community knowledge about these risk factors can be an effective strategy to further reduce the risk of house reinfestation and Chagas transmission.